CRIMINAL OFFENSES AGAINST PROPERTY SEEN FROM AN ANGLE OF BASIC INSTITUTES OF LAW – THINGS AND REAL RIGHTS - Dragana Lazic (University Business Academy in Novi Sad Faculty of Law for Commerce and Judiciary, 2021)
Based on the data from official documents of the Republic Statistical Office and judicial institutions of the Republic of Serbia, the paper analyzes and presents the results of research related to the threat to property and real rights in the Republic of Serbia in the period from 2009 to 2019. We performed the analysis of available data in order to detect the “loss of crime” in a group of crimes aimed at protecting property. The purpose of this paper is a causal analysis of crimes against property in the entire territory of the Republic of Serbia with the aim of revealing causal relations and links between the number of reported, accused and convicted persons for these crimes, to determine the degree of loss of crime and take systemic measures to reduce that loss measure, in accordance with the standards of developed countries.